Heat transfer augmentation of mixture ratio tio2 to sio2 in hybrid nanofluid - K. A., Hamid; W. H., Azmi; M. F., Nabil; R., Mamat (2017)
The efficiency in heat transfer fluid for cooling systems can be improved with the use of hybrid nanofluid. The combination of two or more single nanoparticles in the hybrid nanofluid improve their thermo-physical properties, hence contribute in heat transfer performance. The experimental investigation on forced convection heat transfer of hybrid nanofluid have been carried out on the evaluation of heat transfer coefficient and Nusselt number. The designated working temperature was 30oC, tested for various volume percentage of TiO2 to SiO2. The experiment was conducted in a plain tube under constant heat flux at 7,955 W/m2. The hybrid nanofluid was prepared at 1.0 % volume concentration at three mixture ratios of TiO2 to SiO2. The range of average enhancement in the heat transfer coefficient and Nusselt number observed were 13.6-29.7% and 9.0-17.8%, respectively. The ratio of TiO2 to SiO2 at 20:80 showed the optimum ratio that can be used to obtain maximum enhancement in heat transfer coefficient and Nusselt number. The pressure drop of the hybrid nanofluid increased about double the base fluid for ratio 50:50. Due to the small increment in friction factor which was 1.03 times, the hybrid nanofluid are appropriate for application of cooling systems. It is recommended to use TiO2-SiO2 nanofluid at ratio 20:80 due to its significant enhancement in heat transfer but least increment in friction factor.